Program Kemitraan Masyarakat Dalam Eksplorasi Sumber Zat Warna Organik Di Meruyung Desa Limo Kota Depok - Zulaihah, Lilik; Rahayu, Fajar; Nasution, Siti Rohana; Dewi Munggaran, Nantia Rena (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
Color in a product, both in the form of food products and products other than food, is one thing that makes consumers interested and as a consideration for use or choice. In serving food color as if it will be a must for producers. The dapart staining process is carried out synthetically using chemicals or using natural materials. The use of synthetic dyes has an influence on health and the environment. This makes it an excuse for manufacturers to return to nature by using natural dyes. In the surrounding environment derived from plants, there are many sources of natural dyes both carotenoids, anthocyanin, betalain and chlorophyll. By using the process of exploring plants to produce natural dyes. This natural dye can be applied to food products, and has the ability to maintain health, prevent and minimize the occurrence of several diseases such as diabetes mellitus, hypercholesterolemia, cancer and so on. Therefore, the concept of returning to natural dyes derived from plants so as to maintain health as well as environmental pollution.